Pengaruh Penambahan Ekstrak Touge Sebagai Sumber Nitrogen Alternatif Pada Pembuatan Nata De Salacca - Yusnita Wahyuni Silitonga; Rini Hayati Lubis (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2018)
The application of biotechnology can be used to improve salak economic value. One of salak processed type use microbes by implementation of biotechnology is nata de salacca. The establishment of nata de salacca use of zwavelzure ammonia (ZA) that was alternative nitrogen source relatively dangerous if consumed in quantity more than standard discharging. The objective of this research was to know the effect of touge extract addition on nata de salacca produce. Completely randomized design was applied in this research with three replications. The concentration of touge extract used in this research is 0%, 1%, 2%, 3%. The observer conducted by physical observation such as weight, thickness and rendement of nata. The addition of  1 % touge extract produce 381,6 g of weight and 0,53 cm of thickness. The addition of  3 % touge extract produce 438,6 g of weight and 0,57 cm of thickness. The higher number of touge extrack added so weights and thickness of the nata produse is higher.